2020
DOI: 10.1002/mbo3.1044
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient availability in tropical caves influences the dynamics of microbial biomass

Abstract: Limestone caves are habitats in karst landscapes where surface water sinks into soluble rock in the subsurface and flows in a network of subterranean stream passages (Ford & Willians, 2013). Although hydrological flow regimes, watershed geometry, aqueous geochemistry, and bedrock geology differ between karst areas (Bonacci, Pipan, & Culver, 2008; Simon, Pipan, & Culver, 2007), many caves have similar characteristics and stable environmental conditions, such as temperature and humidity (Griebler et al., 2010; H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…This is reflected in the concentrations of organic carbon, which seems to accumulate at the cave entrance, with its concentration at dark zone site high, in the range of 100 mg g -1 . This supports the conclusions of recent research that although both temperate and tropical cave communities are supported by organic inputs from allochthonous sources, and both types of systems show a trophic gradient from surface to dark zones, the tropical subterranean environments are not limited in energy input to the same degree as their temperate counterparts, due to the diversity and abundance of vegetation and its presence throughout the whole year [3, 5]. The environmental differences between tropical and temperate caves directly influenced the microbial communities within subterranean system.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is reflected in the concentrations of organic carbon, which seems to accumulate at the cave entrance, with its concentration at dark zone site high, in the range of 100 mg g -1 . This supports the conclusions of recent research that although both temperate and tropical cave communities are supported by organic inputs from allochthonous sources, and both types of systems show a trophic gradient from surface to dark zones, the tropical subterranean environments are not limited in energy input to the same degree as their temperate counterparts, due to the diversity and abundance of vegetation and its presence throughout the whole year [3, 5]. The environmental differences between tropical and temperate caves directly influenced the microbial communities within subterranean system.…”
Section: Discussionsupporting
confidence: 89%
“…Salinity was strongly related to the structure of the microbiome at the entrance cave, as previously discussed, and the others environmental drivers were related to dominant saprophytic microorganisms at surface and dark zone. Previous study at TR cave revealed the availability of carbon and nitrogen influenced the microbial strategies for organic matter decomposition and incorporation of those compounds into their biomass [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, such microbial communities have been shown to take part in the formation of caves and sediments influencing several biogeochemical processes. They mainly act as promoters of precipitation or dissolution of minerals in the rock and cave water, which results in the emergence of new formations and speleothems [27][28][29].…”
Section: Microorganisms In Cave Ecosystemsmentioning
confidence: 99%
“…Furthermore, trophic chains in caves are generally regarded as simpler and with communities being characterised by (i) lacking photosynthetic primary producers, (ii) invertebrates that are typically adapted and confined to all aspects of their life cycle underground, and (iii) metabolically active microbes with important biogeochemical activities [9]. While the species diversity of cave macro-organisms is low [10], the diversity of cave micro-organisms can be as high as in surface communities [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%